Characterization of adenylate cyclase from Escherichia coli - Janecek, J; Náprstek, J; Dobrová, Z; Jiresová, M; Spízek, J (Folia microbiologica, 1980)
Adenylate cyclase activity was detected and characterized in cell-free preparations of different strains of Escherichia coli; it was localized not only in the membrane fraction but also in the cytoplasm, the localization differing from strain to strain. The adenylate cyclase activity is highly dependent on the method used for disintegration of cells. The best results were obtained when using vortexing of the cell suspension with ballotini beads. The pH optimum of adenylate cyclase in cell-free preparations was found to be 9.0--9.5. The enzyme has an absolute requirement for Mg2+ and is inhibited by sodium fluoride and inorganic diphosphate. Release of adenylate cyclase from the membrane leads to an immediate loss of the activity; it was found that adenylate cyclase is quite labile and hence it could not yet been purified. The method used to determine adenylate cyclase activity and cyclic AMP is described.
Keywords: hořčík; bezbuněčný systém; Cell Membrane; Cell Fractionation; koncentrace vodíkových iontů; adenylátcyklasy; cytoplazma; Escherichia coli; Cell-Free System; Hydrogen-Ion Concentration; adenosintrifosfát; Magnesium; Sodium Fluoride; buněčná membrána; Phosphates; fluorid sodný; Adenylyl Cyclases; Cytoplasm; fosfáty; frakcionace buněk; Adenosine Triphosphate